(untitled) (Current Problems in Rail Vehicles, 2021)
Adhesive bonding will be ranked with so called special processes where is impossible to absolutely verify the joint quality by means of the following non-destructive tests. The goal of this entry is to describe the adhesive bonded joints questions from the proposal and design, where the suitable adhesive bonding system will be discussed, the adhesive proportions dimensioning etc. to the possible adhesive bonding validation methods including bonded joints calculation analysis.